1995
DOI: 10.1007/bf02425149
|View full text |Cite
|
Sign up to set email alerts
|

A controlled trial of nebulized salbutamol and adrenaline in acute severe asthma

Abstract: After a single dose, nebulized adrenaline (2 mg) proved as effective and safe as salbutamol (5 mg) in acute severe asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Although not directly compared to albuterol, no efficacy or adverse effect differences were found between nebulized epinephrine (an alpha 1 , beta 1 , and B 2 R agonist) and the SABA terbutaline in adults with severe AEA [23,24]. No routine role has been demonstrated in treating AEA in the ED with inhaled use of these agents.…”
Section: Short-acting Beta 2 Agonists (Sabas)mentioning
confidence: 66%
“…Although not directly compared to albuterol, no efficacy or adverse effect differences were found between nebulized epinephrine (an alpha 1 , beta 1 , and B 2 R agonist) and the SABA terbutaline in adults with severe AEA [23,24]. No routine role has been demonstrated in treating AEA in the ED with inhaled use of these agents.…”
Section: Short-acting Beta 2 Agonists (Sabas)mentioning
confidence: 66%
“…One study of adult intensive care unit (ICU) patients (n = 22) with an acute, severe asthma exacerbation found inhaled epinephrine to be as efficacious as salbutamol, with no significant difference in side effects. 2 Another study, using lower doses of epinephrine and salbutamol, also in severe adult asthmatic patients (n = 18), reached similar con- clusions. 3 A third study demonstrated that while in-vitro epinephrine provided greater protection against histamine-induced contraction in airway smooth muscle, this protection was not noted in vivo.…”
mentioning
confidence: 62%
“…This finding is similar to those of one previous small crossover study (n = 10) comparing the efficacies of salbutamol and inhaled epinephrine in admitted asthmatic children 5 and studies in adult patients. 2,3 The two treatments have statistically different effects on heart and respiratory rates, but the changes are too small to be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…10,16,17 A search of MEDLINE and PubMed from 1960 to 2005 using the search terms racemic epinephrine, epinephrine and nebulizers, vapourizers and asthma, airway diseases, or bronchial hyper-reactivity revealed several randomized trials comparing nebulized epinephrine (racemic or regular) to nebulized salbutamol in the initial treatment for acute asthma. [18][19][20][21][22] These studies have all documented increases in pulmonary function and clinical status for nebulized epinephrine that are not statistically different from salbutamol. Side effects were similar between groups receiving either salbutamol or epinephrine, leading several authors to conclude that nebulized epinephrine is as effective and as safe as nebulized salbutamol for the treatment of acute severe asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Side effects were similar between groups receiving either salbutamol or epinephrine, leading several authors to conclude that nebulized epinephrine is as effective and as safe as nebulized salbutamol for the treatment of acute severe asthma. [18][19][20] Finally, a meta-analysis of randomized trials comparing nebulized epinephrine and β 2 -agonists in the initial treatment of acute asthma revealed a non-significant improvement in pulmonary function for patients who received epinephrine, compared with those who received β 2 -agonists. 23 It should be noted that, based on our literature search, no clinical trial was identified that studied the effect of nebulized epinephrine in patients who did not improve with initial salbutamol treatment.…”
Section: Discussionmentioning
confidence: 99%